DNA quality from buccal swabs in neonates: comparison of different storage time (Medical Journal of Indonesia, 2023)
BACKGROUND Genomic medicine has great potential for diagnoses, disease prediction, and targeted treatment. Buccal swabs are a suitable non-invasive method for neonates to obtain DNA samples. Due to Indonesia's geographical conditions, samples require a prolonged time to reach the genetic laboratory. This study aimed to compare the DNA quality of buccal swabs in neonates between immediate and after-storage extraction. METHODS This study was part of a study about the profile of human milk oligosaccharide and FUT2 genotype in Indonesian mother-infant dyads consisting of 20 neonates. 1 swab stick for each participant was taken using a standardized buccal swabbing protocol and divided into 2 isovolume aliquots, which were grouped into the immediate (extraction was performed within 3 days after sampling) and storage groups (extraction was performed on the 14th day after storage in 4°C). DNA yield and purity A260/280 ratio were measured by spectrophotometry. The PCR amplification and Sanger sequencing were performed to validate the DNA isolate quality for downstream application. RESULTS The DNA yield for the immediate group was similar compared with the storage group (9.50 [4.89] versus 9.10 [5.05] µg), p = 0.659, as well as DNA purity A260/280 (1.58 [0.24] versus 1.56 [0.28]), p = 0.785. PCR and sequencing of FUT2 results also showed similar quality between both groups. CONCLUSIONS The similar DNA quality and sequencing results between immediate and storage extraction confirmed that buccal swabs could be stored for 2 weeks, allowing ample time for sample shipping from remote areas to the laboratory.